2018
DOI: 10.1007/s11266-018-0039-2
|View full text |Cite
|
Sign up to set email alerts
|

Examining Patterns of Food Bank Use Over Twenty-Five Years in Vancouver, Canada

Abstract: Food banks have grown substantially in Canada since the 1980s but little is known about patterns or predictors of engagement including frequency or duration of service use. This study examined food bank program data from a large food bank organization in Vancouver, Canada, finding that between January 1992 and June 2017, at least 116,963 individuals made over 2 million food bank visits. The majority of members were engaged for a short time and came for relatively few visits, but 9% of members engaged in longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…In this study, 271 out of 401 participants (67.6%) responded during the final eighteen-month follow-up. Part of the observed attrition could be explained by findings from a large-scale longitudinal study conducted in Vancouver, Canada [ 52 ]. These researchers found that the majority of people who access food banks could be characterized as “short-term, transitional users who visited food banks a handful of times and disengaged after a few weeks or months of use,” and that the 9% who accessed food banks over a long-term accounted for 65% of all food bank visits.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 271 out of 401 participants (67.6%) responded during the final eighteen-month follow-up. Part of the observed attrition could be explained by findings from a large-scale longitudinal study conducted in Vancouver, Canada [ 52 ]. These researchers found that the majority of people who access food banks could be characterized as “short-term, transitional users who visited food banks a handful of times and disengaged after a few weeks or months of use,” and that the 9% who accessed food banks over a long-term accounted for 65% of all food bank visits.…”
Section: Discussionmentioning
confidence: 99%
“…The number of food banks has also expanded dramatically, from 56 Trussell Trust food banks providing a three-day supply of food to the equivalent of 40,989 people in 2009-2010, to more than 2,000 Trussell Trust and independent food banks providing in excess of 1.6 million food parcels in April 2019 (Butler, 2017(Butler, , 2019. Notably, the single most common reason for using Trussell Trust food banks is a problem relating to benefits (Trussell Trust, 2019) and the growth of its network has closely mirrored the chronology of welfare reform (Beck, 2018).…”
Section: Scarcity and Austeritymentioning
confidence: 99%
“…A growing body of research, including on behalf of the Trussell Trust (Loopstra & Lalor, 2017), has shown many of those using food banks need to do so, even if irregularly, on a long-term basis or are unable to afford food for long periods of time (Black & Seto, 2018;Garratt, 2017). Yet the claim that food banks "never turn anyone away empty handed" is clearly fallacious (Beck, 2018).…”
Section: … and Of The Undeserving Poormentioning
confidence: 99%
See 1 more Smart Citation
“…This condition has been associated with reductions in nutritional outcomes ( Bhattacharya et al, 2004 ; Kirkpatrick and Tarasuk, 2008 ; Olson, 1999 ) and negative physical and mental health impacts in children and adults ( Elgar et al, 2021 ; Jones, 2017 ; Ramsey et al, 2011 ; Seligman et al, 2010 ; Stuff et al, 2004 ). Over at least the past four decades food banks and related services have become an essential line of defense against food insecurity in Canadian communities ( Black and Seto, 2020 ; Holmes et al, 2018 ; Riches, 2002 ; Tarasuk et al, 2020 ). In this respect, Canada is not unlike numerous other wealthy countries where a systematic dismantling of the welfare state took place in the intervening period ( Tarasuk et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%